The Follow the Line Method for Quran Memorisation: A Case Study of Grade 3 Students at An Indonesian Islamic Junior High School - Burhanuddin Burhanuddin; Siti Rohimah (Abjadia : International Journal of Education, 2026)
This study aims to describe the implementation and effectiveness of Quran memorization learning using the follow-the-line method for third-grade students at MTs Al-Mukmin. The research method used is a qualitative case study, using observation and in-depth interviews.semi-structured study of 13 third-grade Islamic Junior High School students who met the criteria, and documentation. The results showed that the implementation of Quran memorization learning using the "Follow the Line" method was structured through the stages of reading verses, bolding obscure letters, and reading together. This process helps students become more focused, consistent, and systematic in memorizing. In terms of effectiveness, this method has been proven to improve the quality of student memorization through visual-motor involvement, maintaining learning motivation through various methods, and optimizing the role of teachers as guides, motivators, and correctors. Furthermore, this method also contributes to the development of positive character traits in students, such as discipline, patience, thoroughness, and consistency. Thus, the "Follow the Line" method can be categorized as effective in improving Quran memorization learning and developing student character.